About Edom and Idumea in the Persian period: recent research and approaches from archaeology, Hebrew Bible studies and ancient Near East studies - Hensel, Benedikt; Ben Zvi, Ehud; Edelman, Diana Vikander (Equinox Publishing Ltd, 2022)
Edom and Idumea in the Persian period: an introduction to the volume / by Benedikt Hensel -- The complexity of a site: "Edom" in Persian period from the perspectives of historical research, Hebrew Bible studies and ancient Near Eastern studies / by Benedikt Hensel -- Edom in the Persian period, relations with the Negev, and the Arabian trade: the archaeological evidence / by Piotr Bienkowski -- The genesis of Idumea / by Yigal Levin -- The evolution of an Edomite/Idumean identity: Hellenistic Maresha as a case study / by Ian Stern -- Edom in Judah: identity and social entanglement in the late Iron Age Negev / by Andrew J. Danielson -- Dry climate during the early Persian period and its impact on the establishment of Idumea / by Dafna Langgut and Oded Lipschits -- A tale of two provinces: Judah and Edom during the Persian period / by Alexander Fantalkin and Oren Tal -- Idumean in light of the votive deposits of terracotta figurines / by Adi Erlich -- A monumental Hellenistic-period ritual compound in Upper Idumea: new findings from Ḥorbat 'Amuda / by Michal Haber, Oren Gutfeld and Pablo Betzer -- Edom in the Nabonidus chronicle: a land conquered or a vassal defended? a reappraisal of the annexation of North Arabia by the late Babylonian Empire / by Hanspeter Schaudig -- Have there been prophets in Edom? An ostracon from Ḥorvat 'Uza once more / by Bob Becking -- Economic and administrative Realia of rural Idumea at the end of the Persian period / by Diana V. Edelman -- The Aramaic divination texts / by Esther Eshel, Michael Langlois, and Mark Geller -- Edom as a complex site of memory among the Literati of late Persian/early Hellenistic Judah: some observations / by Ehud Ben Zvi -- Think positive! How the positive portrayal of Edom in late Biblical texts leads to new perspectives on understanding the literary-history of Genesis, Deuteronomy, and Chronicles / by Benedikt Hensel -- The "Edom texts" in Samuel-Kings in inner- and extrabiblical perspective / by Stephen Germany -- Late historical Edom and reading Edom, Seir, and Esau in the prophetic literature through Persian lenses: preliminary observations / by Diana V. Edelman -- The contribution of Chronicles to the memory argument about Edom as reflected in the core repertoire of the Yehudite Literati of the late Persian/Early Hellenistic period / by Ehud Ben Zvi.
Includes bibliographical references and index
Keywords: Edom (Kingdom); Edom (Kingdom) -- Antiquities; Aufsatzsammlung; Vor- und Frühgeschichte; Ausgrabung; Edomiter